2022
DOI: 10.1007/s00396-022-04993-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactant concentration and monomer polarity on particle nucleation in emulsion step polymerization of dithiol with diene

Abstract: The dependence of the number of particles N p as a function of the surfactant concentration [S] is investigated for the step polymerization of dithiol-diene emulsions. A sigmoidal curve for log N p vs log [S] is found for a range of monomers regardless of their polarity. Above the critical micellar concentration (6-20 mM), a N p  [S] x relationship is established with an exponent x dependent on the polarity of the two co-monomers. When the two comonomers are highly water insoluble, x varies typically between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…13 The first investigations showed that the number of polymer particles formed and the nucleation mechanism did not deviate significantly from the normal chain pathway. 14 By contrast, significantly different behaviors are expected regarding polymer MW (evolution throughout the reaction and distribution) and structures (linear, branched, cross-linked and cyclic products), for which very few data are currently available. 15 In contrast to chain polymerization, 16 linear step polymerization is characterized by the difficulty to obtain high MW polymers, which are formed only late in the reaction that is, at very high overall monomer conversions (>98%-99%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The first investigations showed that the number of polymer particles formed and the nucleation mechanism did not deviate significantly from the normal chain pathway. 14 By contrast, significantly different behaviors are expected regarding polymer MW (evolution throughout the reaction and distribution) and structures (linear, branched, cross-linked and cyclic products), for which very few data are currently available. 15 In contrast to chain polymerization, 16 linear step polymerization is characterized by the difficulty to obtain high MW polymers, which are formed only late in the reaction that is, at very high overall monomer conversions (>98%-99%).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other step polymerizations, the formation of high polymers is made possible by distinct characteristic features of the thiol‐ene chemistry: 12 the absence of by‐products, high polymerization rates at ambient temperature (for a wide range of monomers) and a water‐insensitive radical‐mediated polymerization mechanism 13 . The first investigations showed that the number of polymer particles formed and the nucleation mechanism did not deviate significantly from the normal chain pathway 14 . By contrast, significantly different behaviors are expected regarding polymer MW (evolution throughout the reaction and distribution) and structures (linear, branched, cross‐linked and cyclic products), for which very few data are currently available 15 …”
Section: Introductionmentioning
confidence: 99%